2019
DOI: 10.3390/su11133754
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hazard and Vulnerability in Modulating Economic Damages of Inland Floods in the United States Using a Survey-Based Dataset

Abstract: This study investigates the trends in economic damages caused by three types of inland floods (flash flood, flood, and heavy rain) in the United States and the variations in related hazard and vulnerability indicators between 1996 and 2016. We explore the underlying mechanisms based on a survey-based dataset maintained by the National Oceanic and Atmospheric Administration (NOAA) National Weather Service. An annual average of 6518 flood occurrences was reported, which caused economic damages of 3351 million US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Taking into consideration potential changes in water conditions, appropriate measures have to be undertaken in order to minimize the effects of climate change in the future. Numerous analyses showed that undertaking such measures related to reasonable management of water resources is a crucial issue in the case of many countries and in various climate zones [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Case Study and Datamentioning
confidence: 99%
“…Taking into consideration potential changes in water conditions, appropriate measures have to be undertaken in order to minimize the effects of climate change in the future. Numerous analyses showed that undertaking such measures related to reasonable management of water resources is a crucial issue in the case of many countries and in various climate zones [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Case Study and Datamentioning
confidence: 99%
“…The hazards of flash floods are very prominent all over the world [16][17][18][19][20][21][22], causing quite painful life and economic losses [23]. For example, a case study of the Erbil-Kurdistan region of Iraq shows that compared with developed countries, flash floods are more destructive in less developed areas [24].…”
Section: Introductionmentioning
confidence: 99%
“…During 1995-2015, 2.3 billion people were affected by floods, with total damage losses of $662 billion worldwide [10]. A flood hazard assessment can provide important information for decision-makers to better understand the flood risk and, further, strategically reduce flood losses [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%